A history of the study of the indigenous languages of North America - Kilarski, Marcin (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences ;, 2021)
"The languages indigenous to North America are characterized by a remarkable genetic and typological diversity. Based on the premise that linguistic examples play a key role in the origin and transmission of ideas within linguistics and across disciplines, this book examines the history of approaches to these languages through the lens of some of their most prominent properties. These properties include consonant inventories and the near absence of labials in Iroquoian languages, gender in Algonquian languages, verbs for washing in the Iroquoian language Cherokee and terms for snow and related phenomena in Eskimo-Aleut languages. By tracing the interpretations of the four examples by European and American scholars, the author illustrates their role in both lay and professional contexts as a window onto unfamiliar languages and cultures, thus allowing a more holistic view of the history of language study in North America"--